2004
DOI: 10.1002/hlca.200490045
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Acyclic Nitroazole Nucleosides and Their Incorporation into Oligonucleotides, and Their Duplex and Triplex Formation

Abstract: Acyclic nucleosides of 4-nitro-1H-imidazole and 4-nitropyrazole have been synthesized by nucleophilic addition of the appropriate 4-nitroazole to (À)-(S)-(hydroxymethyl)oxirane in the presence of a catalytic amount of potassium carbonate. ()-(R)-3-(4-nitro-1H-imidazol-1-yl)propane-1,2-diol and ()-(R)-3-(2-methyl-4-nitro-1H-imidazol-1-yl)propane-1,2-diol were also obtained in an independent reaction starting from appropriate 1,4-dinitro-1H-imidazole and ()-(R)-3-aminopropane-1,2-diol. ()-(R)-3-(4-Nitropyrazol-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…These authors found that all the modified bases led to destabilized triplexes, and confirmed the report that 3-nitropyrrole (1) destabilized triplex formation [79][80][81]. Similar data were observed for the stability of acyclic nitroazole nucleosides in triplexes [82]. However, further studies showed that stable triplexes containing 1 in the third strand can be obtained in the presence of benzopyridoindole.…”
Section: Applications Of Universal Base Analoguessupporting
confidence: 73%
“…These authors found that all the modified bases led to destabilized triplexes, and confirmed the report that 3-nitropyrrole (1) destabilized triplex formation [79][80][81]. Similar data were observed for the stability of acyclic nitroazole nucleosides in triplexes [82]. However, further studies showed that stable triplexes containing 1 in the third strand can be obtained in the presence of benzopyridoindole.…”
Section: Applications Of Universal Base Analoguessupporting
confidence: 73%
“…73 Experience gathered in the application of the ANRORC reaction in syntheses of nucleosides was expanded by Walczak et al to acyclic nucleosides. 74 The ANRORC reaction of compounds 1 and 2 was applied for conversion of unprotected 2-amino-2-deoxy-D-hexopyranoses into 2-deoxy-2-(4′-nitro-1′H-imidazol-1′-yl)-D-hexopyranoses. The obtained mixtures of anomers were separated into pure products following acetylation.…”
Section: Wengel Andmentioning
confidence: 99%
“…7) into oligonucleotides. 60 Thermal melting studies of duplexes of the oligonucleotides with 4-nitropyrazole or 4-nitro-1H-imidazole paired with four natural bases showed that the acyclic 4-nitro-1H-imidazole (R) gave a range of 4 uC, while the 2-methyl-4-nitro-1H-imidazole (R), 4-nitro-1H-pyrazole (R) and 4-nitro-1H-pyrazole (S) each gave a very narrow range of 2 uC. The duplexes from oligonucleotides with the sugar 3-nitropyrrole in the middle of a T region were reported to melt by 11-14 uC lower than the corresponding sequences containing an A?T base pair, whereas for the 26-mer only a 5-10 uC lower melting temperature was observed for all the investigated acyclic azoles in a T region when compared with the A?T base pair.…”
Section: Acyclic Nitroazolesmentioning
confidence: 99%